2017
DOI: 10.3847/1538-4357/aa8327
|View full text |Cite
|
Sign up to set email alerts
|

Deep Imaging of the HCG 95 Field. I. Ultra-diffuse Galaxies

Abstract: We present a detection of 89 candidates of ultra-diffuse galaxies (UDGs) in a 4.9 degree 2 field centered on the Hickson Compact Group 95 (HCG 95) using deep g-and r-band images taken with the Chinese Near Object Survey Telescope. This field contains one rich galaxy cluster (Abell 2588 at z=0.199) and two poor clusters (Pegasus I at z=0.013 and Pegasus II at z=0.040). The 89 candidates are likely associated with the two poor clusters, giving about 50 − 60 true UDGs with a half-light radius r e > 1.5 kpc and a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 76 publications
1
58
0
10
Order By: Relevance
“…Deep imaging observations reveal the existence of a population of low central surface brightness (µ g,0 > 24 mag.arcsec −2 ) galaxies with stellar masses of dwarfs and effective radii comparable to that of the Milky Way (r eff > 1.5 kpc). These Ultra Diffuse Galaxies (UDGs) appear to be ubiquitous in groups and clusters (e.g., van Dokkum et al 2015a,b;Janowiecki et al 2015;Koda et al 2015;Muñoz et al 2015;Mihos et al 2015Mihos et al , 2017Merritt et al 2016;van der Burg et al 2016;Yagi et al 2016;Janssens et al 2017;Shi et al 2017) but are also observed in the field (e.g., Román & Trujillo 2017;Leisman et al 2017). Spectroscopic studies of a few cases indicate intermediate to old, metal poor stellar populations for UDGs in groups and clusters (Ferré-Mateu et al 2018;Gu et al 2018;Ruiz-Lara et al 2018) while the spectral energy distribution (SED) fitting of a field UDG points towards younger stellar populations in the field (Pandya et al 2018).…”
Section: Ultra Diffuse Galaxiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Deep imaging observations reveal the existence of a population of low central surface brightness (µ g,0 > 24 mag.arcsec −2 ) galaxies with stellar masses of dwarfs and effective radii comparable to that of the Milky Way (r eff > 1.5 kpc). These Ultra Diffuse Galaxies (UDGs) appear to be ubiquitous in groups and clusters (e.g., van Dokkum et al 2015a,b;Janowiecki et al 2015;Koda et al 2015;Muñoz et al 2015;Mihos et al 2015Mihos et al , 2017Merritt et al 2016;van der Burg et al 2016;Yagi et al 2016;Janssens et al 2017;Shi et al 2017) but are also observed in the field (e.g., Román & Trujillo 2017;Leisman et al 2017). Spectroscopic studies of a few cases indicate intermediate to old, metal poor stellar populations for UDGs in groups and clusters (Ferré-Mateu et al 2018;Gu et al 2018;Ruiz-Lara et al 2018) while the spectral energy distribution (SED) fitting of a field UDG points towards younger stellar populations in the field (Pandya et al 2018).…”
Section: Ultra Diffuse Galaxiesmentioning
confidence: 99%
“…Although the abundance of globular clusters in UDGs compared to dwarf galaxies of similar masses displays a significant scatter, its often large value may indi-cate intense star formation episodes in the past Peng & Lim 2016;van Dokkum et al 2016van Dokkum et al , 2017Lim et al 2018;Amorisco et al 2018). Some UDGs also seem to harbour signs of recent or ongoing star formation (Martínez-Delgado et al 2016;Trujillo et al 2017;Shi et al 2017;Pandya et al 2018) while both Janowiecki et al (2015) and Shi et al (2017) report group UDGs rich in atomic HI gas. Martín-Navarro et al (2019) further interpret the high [Mg/Fe] abundance ratio of a field UDG with an extended star formation history as a possible result of supernova-driven gas outflows.…”
Section: Ultra Diffuse Galaxiesmentioning
confidence: 99%
“…The detection of populations of UDGs in galaxy clusters (e.g. van Dokkum et al 2015;Mihos et al 2015;van der Burg et al 2016;Venhola et al 2017;Shi et al 2017) led to the exploration of a possible evolutionary link between these galaxies and their harsh environment (Safarzadeh & Scannapieco 2017;Conselice 2018;Ogiya 2018;Bennet et al 2018;Carleton et al 2019). However, UDGs were also found in less dense environments, such as filaments (e.g.. Martínez-Delgado et al 2016), groups (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Follow-up observations have shown these assumptions to be generally accurate, but sometimes UDGs can be members of more distant background structures (e.g., Danieli et al 2017). Even given these challenges, recent work has identified hundreds of UDGs in new and archival observations across all environments: galaxy clusters (Mihos et al 2015;Wittmann et al 2017), groups (Merritt et al 2016;Smith Castelli et al 2016;Shi et al 2017), filaments (Martínez-Delgado et al 2016), and the field (Papastergis et al 2017;Leisman et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Searches for 21cm emission have focused on UDGs in isolation, where H is more likely to persist (Bellazzini et al 2015;Leisman et al 2017;Papastergis et al 2017). Recent work has also detected H in optically blue UDGs that are a members of Hickson Compact Groups ) and a relatively poor galaxy cluster (Shi et al 2017). However, a deep search for H from NGC1052-DF2 yielded a non-detection (Chowdhury 2019).…”
Section: Introductionmentioning
confidence: 99%